Development of a guidebook for implementing the seven habits of great Indonesian children in early childhood education - Ester Tri Lestari; Sri Utaminingsih; Erik Aditia Ismaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Character habituation in early childhood frequently breaks down at home, so the seven habits promoted by the Indonesian Ministry of Primary and Secondary Education are internalized inconsistently. This study aimed to develop a school–family collaborative guidebook for implementing the seven habits in early childhood education and to determine its validity, practicality, and implementation outcomes. The ADDIE model was applied at Rajawali Kindergarten, Juwana, from February to May 2025. Six experts and practitioners assessed the product using a 16-item, four-point questionnaire, while implementation with 46 children aged 3–6 years was studied qualitatively through observation, interviews, and daily journals, with trustworthiness established through triangulation and peer checking. Validation reached 97.7% overall content 97.5%, language 96.9%, presentation and design 96.9%, and 100% for practicality, placing the guidebook in the very feasible category. During implementation, positive responses ranged from 58% to 88% among parents and from 70% to 98% among teachers, the school–home gap reaching 38 percentage points for eating healthy food. The guidebook and its journal are therefore feasible for sustaining habituation across both settings, although habits governed by household routines change more slowly. Schools should pair the guidebook with parenting sessions and periodic journal review.